Effects of mind–body therapies on depression among adolescents: a systematic review and network meta-analysis - Luo, Shulai; Mei, Zhengyang; Fang, Guisong; Mu, Guogang; Zhang, Xiuying; Luo, Shi (Frontiers in Public Health, 2024)
Background: Depression poses significant threats to adolescents' health globally. Research has shown the potential of mind-body therapies to alleviate depression, but limited studies have directly compared the therapeutic effects of different types of mind-body therapies on adolescent depression and the optimal therapy remain unclear. Therefore, we conducted a systematic review and network meta-analysis of randomized controlled trials that met the inclusion criteria to explore the effectiveness of different types of mind-body therapies as interventions to improve depression among adolescents, and to identify the most effective interventions. Methods: A comprehensive search of databases including PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus up to January 2024 was conducted to assess the impact of mind-body therapies on depression among adolescents. The risk of bias of the included studies was evaluated using Cochrane Review Manager 5.4. STATA 18.0 was used for network meta-analysis. The nodesplitting method was used to test the local inconsistency of the network meta-analysis. Funnel plots and the Egger's test were utilized to assess the potential impact of bias in this study. Result: This network meta-analysis included 9 randomized controlled trials involving a total of 955 subjects. The results indicated that yoga, dance therapy and tai chi were more effective than other mind-body therapies in reducing symptoms of depression among adolescents. Specifically, according to the SUCRA ranking, yoga was rated to be the optimal intervention for adolescents with depression (SCURA: 82.2%), followed by dance therapy (SCURA: 77.5%) and tai chi (SCURA: 64.9%). Conclusion: This study revealed that mind-body therapies have positive effects on improving depression among adolescents. Yoga may be the most effective intervention among the different types of mind-body therapies. However, due to the small sample size of patients included, the certainty of the results was limited to some extent. Therefore, further investigation is necessary to strengthen the evidence base when more relevant studies become available.